2004
DOI: 10.1097/00006982-200410001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Guidelines for Intravitreous Injections

Abstract: Intravitreous (i.v.t.) injection is increasingly being incorporated into the management of ocular diseases. While only fomivirsen sodium (Vitravene) is currently approved by the Food and Drug Administration as an i.v.t. injection, the number of approved i.v.t. injections indications is anticipated to grow on the basis of promising results from ongoing clinical studies. Despite the potential benefits that may be derived from intraocular injections of different agents, no guidelines have been published previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
232
1
55

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(291 citation statements)
references
References 25 publications
3
232
1
55
Order By: Relevance
“…The findings of this study showed that a majority of treating ophthalmologists reported use of gloves, draping, pre-injection topical antibiotics, povidone–iodine, eyelid speculum, and post-injection topical antibiotics when performing IVT injections as recommended by the guidelines 3. Thus, it was concluded that treating ophthalmologists had a good adherence to all aspects of the guidelines on IVT injections.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The findings of this study showed that a majority of treating ophthalmologists reported use of gloves, draping, pre-injection topical antibiotics, povidone–iodine, eyelid speculum, and post-injection topical antibiotics when performing IVT injections as recommended by the guidelines 3. Thus, it was concluded that treating ophthalmologists had a good adherence to all aspects of the guidelines on IVT injections.…”
Section: Discussionmentioning
confidence: 71%
“…It is important to note that educational materials and two published articles on treatment guidelines of IVT injections2,3 were distributed at the investigator meetings prior to patient enrollment. Although the authors would like to draw a direct conclusion between the introduction of educational materials and the adherence to the guidelines, as noted, the questionnaires only assess knowledge rather than actual behavior; the authors consider the introduction of educational materials may provide reinforcement of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no studies have yet been reported that assess pharmacokinetic and pharmacodynamic activity of ASO after intravesical delivery in humans, preclinical studies would suggest that ASO are taken up by urothelium (47,48). Interestingly, the only approved clinical indication for an ASO is for intravitreal injection of cytomegalovirus-induced retinitis in human immunodeficiency virus, illustrating the potential clinical utility of local instillation for this class of therapeutics (49).…”
Section: Ogx-427 Down-regulation Of Hsp27 In Bladder Cancermentioning
confidence: 99%
“…The current recommendation for performing intravitreal injections advises against performing a paracentesis. 1 However, in patients who suffer from glaucoma or optic nerve damage, there is a concern that a transient high IOP elevation may further damage the ganglion cells in the optic nerve. It is important to know the transient IOP elevations that patients are subjected to after such intravitreal injections for several reasons, such as to assess whether a paracentesis is necessary, whether IOP monitoring is necessary after the procedure, and to reassess, when manufacturing a new drug, the optimum amount of fluid to be injected into the eye.…”
Section: Introductionmentioning
confidence: 99%